Decreased Cytochrome P450 3A activity in palliative patients with haematological diseases: Potential impact on supportive drug therapies. Issue 2 (15th April 2019) - Geist, Marcus J. P.; Siller, Nelly; Egerer, Gerlinde; Bardenheuer, Hubert; Burhenne, Juergen; Mikus, Gerd
Abstract: Cytochrome P450 3A (CYP3A) is the most relevant drug‐metabolizing enzyme in human beings involved in the elimination of about 50% of the marketed drugs. Comprehensive in vivo data of CYP3A activity in palliative patients with haematological diseases are missing. Therefore, CYP3A activity was determined under real‐life clinical conditions in patients to gain knowledge about dose adjustments for supportive therapies and symptom management in haematology. The single‐arm, prospective trial obtained a 4‐hours pharmacokinetic profile of midazolam after oral administration of a microdose as marker substance from each enrolled patient. Plasma concentrations of midazolam and its primary metabolite 1′‐hydroxy‐midazolam were quantified by mass spectrometry techniques. CYP3A activity was calculated as partial metabolic clearance from an established limited sampling area under the curve. All other drugs taken by the participating patients were considered as well as recent laboratory test results and the patients' diagnoses. Partial metabolic clearance of midazolam in patients with haematological diseases was highly variable (36.9 ± 52.7 L/h). In comparison with the CYP3A activity of healthy individuals, this was a highly significant 30% reduction of activity ( P  < 0.0001). Dosing of major CYP3A substrate drugs needs to be reduced in palliative patients with haematological diseases, otherwise escalation of debilitating symptoms due to drug interactions might occur.